Skeletal muscle surrogates for the acquisition of muscle repair skills in upper limb surgery. (July 2022) - Heskin, Leonie; Galvin, Rose; Conroy, Jack; Traynor, Oscar; Madden, Stephen; Simms, Ciaran
Abstract: Introduction: The required fidelity of synthetic materials in surgical simulators to teach tissue handling and repair requirements should be as accurate as possible. There is a poor understanding of the relationship between choice of muscle surrogates and training outcome for trainee surgeons. To address this, the mechanical characteristics of several candidate synthetic muscle surrogates were measured, and their subjective biofidelity was qualitatively assessed by surgeons. Methods: Silicone was selected after assessing several material options and 16 silicone-based surrogates were evaluated. Three of the closest samples to muscle (Samples 1.1, 1.2, 1.3) and one with inserted longitudinal fibres (1.2F) were mechanically tested in the following: compression and tension, needle puncture force and suture pull-out in comparison with real muscle. The four samples were evaluated by 17 Plastic and Orthopaedic surgeons to determine their views of the fidelity with regard to the handling properties, needle insertion and ease of suture pull-out. Results: The mechanical testing showed the surrogates exhibited varying characteristics that matched some of the properties of muscle, though none recreated all the mechanical characteristics of native muscle. Good biofidelity was generally achieved for compression stiffness and needle puncture force, but it was evident that tensile stiff was too low for all samples. The pull-out forces were variable and too low, except for the sample with longitudinal fibres. In the qualitative assessment, the overall median scores for the four surrogate samples were all between 30 and 32 (possible range 9–45), indicating limited differentiation of the samples tested by the surgeons. Conclusions: The surrogate materials showed a range of mechanical properties bracketing those of real muscle, thus presenting a suitable combination of candidates for use in simulators to attain the requirements as set out in the learning outcomes of muscle repair. However, despite significant mechanical differences between the samples, all surgeons found the samples to be similar to each other. Graphical abstract: Image 1 Highlights: Four silicone based muscle surrogates tested for suitability for a simulator. Surrogates tested in tension, compression, puncture and suture pull-out force. Surrogates mimicked muscle in compression and puncture force. Surgical experts rated the samples compared to that during in-vivo muscle repair.